2011
DOI: 10.1016/j.vaccine.2011.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants that stimulate TLR3 or NLPR3 pathways enhance the efficiency of influenza virus-like particle vaccines in aged mice

Abstract: There is intense interest in the design and use of vaccine strategies against influenza to enhance protective immune responses in the elderly. To address the need for improved influenza vaccines for the aged, two inflammatory adjuvants, Imject(®) alum (a stimulator of the Nod-like receptor, Nalp3) and poly I:C (a toll-like receptor type 3 ligand), were used during vaccination with novel influenza virus-like particles (VLP). Adult (4 month old) or aged (24 month old) mice were vaccinated with VLPs alone or in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 60 publications
(72 reference statements)
1
35
0
Order By: Relevance
“…Our results, together with emerging reports on other pattern recognition receptors33, 36, 42, strongly support further clinical studies on the roles of innate immunity in controlling influenza and to explore potential applications of receptor targeting, especially as preventive interventions 2, 4, 37…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results, together with emerging reports on other pattern recognition receptors33, 36, 42, strongly support further clinical studies on the roles of innate immunity in controlling influenza and to explore potential applications of receptor targeting, especially as preventive interventions 2, 4, 37…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, recent studies have shown that TLR's role in regulating the adaptive responses can be harnessed to boost immunogenicity of influenza vaccines (e.g., TLR9 or TLR7 ligands as adjuvants). This may be particularly useful in the elderly and the immunologically naïve vaccinees 4, 33, 34, 35, 36, 37, 38, 39, 40. Our data in natural influenza provide additional support to this new vaccination approach.…”
Section: Discussionmentioning
confidence: 65%
“…This was an unexpected finding, yet to be explained or confirmed, but which similar to SU inactivated influenza vaccines contradicted findings from animal studies [87]. Given our current experience from clinical studies with alum-adjuvanted influenza A/H5N1 vaccines in humans and animals, preformulation studies of alum-adjuvanted vaccines will likely be beneficial and minimize potential issues related to suboptimal formulations.…”
Section: Expert Commentarymentioning
confidence: 82%
“…In the context of VLP vaccinology, Poly I:C has been shown to enhance the protective ability of a VLP-based vaccine against a lethal challenge in a mouse model using a mouse-adapted flu virus [84]. In addition, a VLP-based vaccine for Ebola virus was more efficacious in mice and guinea pigs when adjuvanted with Poly ICLC adjuvant (Hiltonol, Oncovir Inc.) which is a stable combination of Poly IC and Poly lysine [85].…”
Section: Classes Of Adjuvants Tested For Vlp-based Vaccinesmentioning
confidence: 99%